Mining protein complexes from protein interaction data - Wu, Min (2013)
Protein complexes play key roles in various important cellular processes, such as transcription, translation and so on. However, experimental detection of protein complexes is very time-consuming and tedious. That is why currently we still have only a limited number of known protein complexes. Therefore, computational methods are highly desired to generate high-quality candidates of protein complexes for wetlab validation. Meanwhile, protein complexes are analyzed to have substructures, i.e., a protein complex has several proteins to form a core and other proteins in periphery as attachments. Although there are already many computational methods for detecting protein complexes from PPI data, most of them fail to reveal this inherent organization of protein complexes.